Penerapan Metode C4.5 Untuk Memprediksi Permintaan Bahan Baku - Syah, Irwan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Predicting demand for raw materials is one of the important things that PT. Arma of Eternal Grace. However, there are still obstacles such as excessive accumulation of raw materials in each branch store. So we need to predict so that in the future when we enter moments such as Eid al-Fitr, New Year, Chinese New Year and Christmas we can handle them so that there is no accumulation of raw materials so as not to cause losses to the PT company. Arma of Eternal Grace. Therefore, calculations are needed when predicting raw materials that are more accurate and well controlled. The C4.5 algorithm method is a method used to predict demand for raw materials in branch stores to make it more efficient and controlled so that there are no shortages or excesses in each branch store. The result of this research is the application of data mining using the C4.5 algorithm method which can predict demand for raw materials with more accurate decisions in the future.